Are women with gestational diabetes being screened for type 2 diabetes following pregnancy? A nationwide retrospective cohort study in Aotearoa New Zealand. (December 2022) - Sise, Andrew; Donald, Sarah; Coppell, Kirsten J.; Barson, David; Crengle, Sue; Parkin, Lianne
Highlights: 53.3% of women received appropriate screening within six months postpartum. Inequity in postpartum type 2 diabetes screening was identified for Māori women. Postpartum type 2 diabetes screening varied widely by geographic region. Administrative data are viable for monitoring postpartum type 2 diabetes screening. Abstract: Aim: To estimate the proportion of women with a first episode of gestational diabetes mellitus (GDM) in Aotearoa (New Zealand) who received postpartum screening for type 2 diabetes mellitus (T2DM). Methods: Data from 941, 468 pregnancies occurring between 2005 and 2015 were linked with laboratory, community pharmacy, and hospital discharge data from the Ministry of Health's National Collections to identify a cohort of women who had a first episode of GDM (n = 14, 443). Proportions receiving a glycated haemoglobin (HbA1c) test or oral glucose tolerance test (OGTT) during the first year postpartum were estimated overall, and by calendar year, ethnic group, age, deprivation, and region. Results: Overall, 40.9% (95% CI 40.1–41.7%) received an HbA1c test or OGTT within 3 months, 53.3% (52.5–54.1%) within 6 months, and 61.0% (60.2–61.8%) within 12 months postpartum. Screening proportions within 12 months were stable over time. Indigenous Māori were less likely to receive screening within 6 months postpartum (35.0% [33.1–37.0%]) than other ethnic groups, as were younger women and those with higher deprivation. There were marked variations by region (between 15.3% and 67.5%). Conclusion: Postpartum T2DM screening was low over the period studied, with substantial ethnic and regional inequities across New Zealand.